MODEL PENGEMBANGAN KEMAMPUAN PRA-MEMBACA-MENULIS BERBASIS KARAKTER - Widuroyekti, Barokah; Sulistiyono, Sulistiyono (LPPM Universitas Terbuka, 2014)
The article draws on research that aims to develop a model of the development of pre-reading-writing ability of a character-based education in kindergarten. The study was used the Research and Development method involving teachers and children at three kindergartens in Jombang. The procedure consists of two phases study, the preliminary studies and model development. Data collected by observation, interviews, documentation, questioner techniques, validation testing experts, and the results are analyzed with qualitative analysis techniques. The results showed that teachers require manual and development model's to pre-reading-writing ability of a character-based, as well as scenario development activity. The model of development gives the possibility for children to develop the ability to recognize text and pre-reading-writing through story. Development model cantains character values on planning, include: objectives, materials, and activities, as well as the implementation, include: introduction, core, and closing activities. Artikel ini disusun berdasarkan penelitian yang bertujuan mengembangkan model pengembangan kemampuan pra-membaca-menulis berbasis pendidikan karakter di TK. Penelitian dilakukan menggunakan pendekatan penelitian pengembangan melibatkan guru-guru dan anak-anak di tiga TK Kabupaten Jombang. Prosedur penelitian terdiri atas dua tahap, yakni studi pendahuluan dan pengembangan model. Data dikumpulkan dengan teknik observasi, wawancara, dokumentasi, kuesioner dan uji validasi pakar, serta hasilnya dianalisis dengan teknik analisis kualitatif. Hasil penelitian menunjukkan bahwa guru membutuhkan panduan dan model pengembangan kemampuan pra-membaca-menulis berbasis karakter, serta skenario kegiatan pengembangan. Model pengembangan yang dihasilkan memungkinkan anak mengenal tulisan dan mengembangkan kemampuan pra-membaca-menulis melalui cerita. Model pengembangan memuat nilai karakter pada komponen perencanaan, meliputi: tujuan, materi, dan kegiatan, serta pada pelaksanaan meliputi: pendahuluan, inti, dan penutup.